Wild-Type p53-Induced Phosphatase 1 Plays a Positive Role in Hematopoiesis in the Mouse Embryonic Head - He, Wenyan; Zhang, Ying; Cao, Zhan; Ye, Zehua; Lu, Xun; Fan, Junwan; Peng, Wei; Li, Zhuan (Frontiers in Cell and Developmental Biology, 2021)
The first adult repopulating hematopoietic stem cells (HSCs) are found in the aorta-gonad-mesonephros (AGM) region, which are produced from hemogenic endothelial cells. Embryonic head is the other site for HSC development. Wild-type p53-induced phosphatase 1 (Wip1) is a type-2Cδ family serine/threonine phosphatase involved in various cellular processes such as lymphoid development and differentiation of adult HSCs. Most recently, we have shown that Wip1 modulates the pre-HSC maturation in the AGM region. However, it is not clear whether Wip1 regulates hematopoiesis in the embryonic head. Here we reported that disruption of Wip1 resulted in a decrease of hematopoietic progenitor cell number in the embryonic head. In vivo transplantation assays showed a reduction of HSC function after Wip1 ablation. We established that Wip1 deletion reduced the frequency and cell number of microglia in the embryonic head. Further observations revealed that Wip1 absence enhanced the gene expression of microglia-derived pro-inflammatory factors. Thus, it is likely that Wip1 functions as a positive regulator in HSC development by regulating the function of microglia in the embryonic head.